Associations between School-Level Disadvantage, Bullying Involvement and Children's Mental Health - Julia R. Badger; Mirela Zaneva; Richard P. Hastings; Matthew R. Broome; Rachel Hayes; Paul Patterson; Naomi Rose; Suzy Clarkson; Judy Hutchings; Lucy Bowes (MDPI AG, 2023)
Bullying is a modifiable risk factor for poor mental health across childhood and adolescence. It is also socially patterned, with increased prevalence rates in more disadvantaged settings. The current study aimed to better understand whether school-level disadvantage is associated with different types of bullying roles, and whether it is a moderator in the association between bullying and children's mental health. Cross-sectional data were used from 4727 children aged 6-11 years, from 57 primary schools across England and Wales. The child data included previous bullying involvement and bullying role characteristics (bully, victim, bully-victim, reinforcer, defender, outsider), and the teacher-reported data included each child's mental health (emotional symptoms and externalizing) problems. School-level disadvantage was calculated from the proportion of children in the school eligible to receive free school meals (an indicator of disadvantage). Children in more disadvantaged schools were more likely to report being bully perpetrators, bully-victims, and engage less in defending behaviors during a bullying incident. Children from more disadvantaged schools who reported bullying others showed fewer emotional symptoms than those from less disadvantaged schools. There was no other evidence of moderation by school-level disadvantage between bullying roles and emotional and externalizing problems. The findings highlight the potential for school-based interventions targeting children's emotional and social development, targeting bullying, and promoting defending behaviors, particularly in more disadvantaged settings.